Fat in the Fossa and the Sphenoid Sinus: A Simple and Effective Solution to CSF Leaks in Transsphenoidal Surgery. Cohort Study and Systematic Review - Baig Mirza, Asfand; Boardman, Timothy; Okasha, Mohamed; El-Hariri, Hazem Mohamed; Al Banna, Qusai; Syrris, Christoforos; Baig Mirza, Kaumal; Vastani, Amisha; Visagan, Ravindran; Shapey, Jonathan; Maratos, Eleni; Barazi, Sinan; Thomas, Nick (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objectives Cerebrospinal fluid (CSF) leak following endoscopic transsphenoidal surgery (TSS) remains a challenge and is associated with high morbidity. We perform a primary repair with fat in the pituitary fossa and further fat in the sphenoid sinus (FFS). We compare the efficacy of this FFS technique with other repair methods and perform a systematic review.Design, Patients, and Methods This is a retrospective analysis of patients undergoing standard TSS from 2009 to 2020, comparing the incidence of significant postoperative CSF rhinorrhea (requiring intervention) using the FFS technique compared with other intraoperative repair strategies. Systematic review of current repair methods described in the literature was performed following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines.Results In all, there were 439 patients, with 276 patients undergoing multilayer repair, 68 patients FFS repair, and 95 patients no repair. No significant differences were observed in baseline demographics between the groups. Postoperative CSF leak requiring intervention was significantly lower in the FFS repair group (4.4%) compared with the multilayer (20.3%) and no repair groups (12.6%, p < 0.01). This translated to fewer reoperations (2.9% FFS vs. 13.4% multilayer vs. 8.4% no repair, p < 0.05), fewer lumbar drains (2.9% FFS vs. 15.6% multilayer vs. 5.3% no repair, p < 0.01), and shorter hospital stay (median days: 4 [3–7] FFS vs. 6 (5–10) multilayer vs. 5 (3–7) no repair, p < 0.01). Risk factors for postoperative leak included female gender, perioperative lumbar drain, and intraoperative leak.Conclusion Autologous fat on fat graft for standard endoscopic transsphenoidal approach effectively reduces the risk of significant postoperative CSF leak with reduced reoperation and shorter hospital stay.
Keywords: transsphenoidal; endoscopic; CSF leak; repair; sellar; fat graft